The effect of insulin-loaded chitosan particle-aggregated scaffolds in chondrogenic differentiation - Malafaya, P. B. (2010)
Osteochondral defect repair requires a tissue engineering approach that aims at mimicking the physiological properties and structure of two different tissues (cartilage and bone) using a scaffold–cell construct. One ideal approach would be to engineer in vitro a hybrid material using a single-cell source. For that purpose, the scaffold should be able to provide the adequate biochemical cues to promote the selective but simultaneous differentiation of both tissues. In this work, attention was paid primarily to the chondrogenic differentiation by focusing on the development of polymeric systems that provide biomolecules release to induce chondrogenic differentiation. For that, different formulations of insulin-loaded chitosan particle–aggregated scaffolds were developed as a potential model system for cartilage and osteochondral tissue engineering applications using insulin as a potent bioactive substance known to induce chondrogenic differentiation. The insulin encapsulation efficiency was shown to be high with values of 70.37!0.8%, 84.26!1.76%, and 87.23!1.58% for loadings of 0.05%, 0.5%, and 5%, respectively. The in vitro release profiles were assessed in physiological conditions mimicking the cell culture procedures and quantified by Micro-BCA! protein assay. Different release profiles were obtained that showed to be dependent on the initial insulin-loading percentage. Further, the effect on prechondrogenic ATDC5 cells was investigated for periods up to 4 weeks by studying the influence of these release systems on cell morphology, DNA and glycosaminoglycan content, histology, and gene expression of collagen types I and II, Sox-9, and aggrecan assessed by real-time polymerase chain reaction. When compared with control conditions (unloaded scaffolds cultured with the standard chondrogenic-inducing medium), insulin-loaded scaffolds upregulated the Sox-9 and aggrecan expression after 4 weeks of culture. From the overall results, it is reasonable to conclude that the developed loaded scaffolds when seeded with ATDC5 can provide biochemical cues for chondrogenic differentiation. Among the tested formulations, the higher insulin-loaded system (5%) was the most effective in promoting chondrogenic differentiation.